The Definitive Guide to Magento A Comprehensive Look at Magento - McCombs, Adam.; Banh, Robert; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
This book takes a comprehensive look at Magento, a robust and flexible e-commerce platform built on the Zend framework. With more than 750,000 downloads, Magento is the fastest growing open source e-commerce solution. This book walks you through all of the steps necessary to build a fully functional Magento-based web site. It also includes information on managing products, customers, and orders. This book is directed at web site designers and developers, but will also be extremely useful for business owners who have web sites built on the Magento platform. Introduces you to Magento, the fastest-growing open-source e-commerce platform Demonstrates how to configure and use Magento Covers how to customize Magento and develop extensions for the Magento platform
Getting Started with Magento -- to Magento -- Installing Magento -- The Public Interface Walk-through -- The Administration Interface Walk-through -- Working with Products -- Working with Customers -- Advanced Magento Development -- Working with Orders -- Configuring Magento -- Customizing Magento$1 (Bs Appearance -- Magento Extensions -- API -- Tips and Tricks.s
Keywords: Computer science; Computer Science; e-Commerce/e-business.